Prevalence of mineralization in the pulp chamber in patients according to CBCT data - V. A. Molokova; I. N. Antonova; V. A. Osipova (Эндодонтия Today)
INTRODUCTION. Pulp calcifications, first described as denticles by Norman and Johnson in 1921, are classified as pulp stones, calcifications, or obliterations of the tooth cavity. These conditions are often asymptomatic and detectable only by imaging, with cone-beam computed tomography (CBCT) offering highresolution, three-dimensional visualization. Pulp canal calcifications complicate endodontic treatment by increasing the risk of perforation and making canal negotiation difficult. Although various etiological factors have been proposed – including aging, genetics, trauma, restorations, and systemic conditions – the exact causes remain unclear. Data on the prevalence of pulp calcifications in the Russian Federation, particularly in the Northwest region, are currently lacking. AIM. This study aimed to retrospectively investigate the occurrence of pulp canal obliteration and calcific deposits within the tooth cavity through cone-beam computed tomography (CBCT) analysis. MATERIALS AND METHODS. The study included 102 patients (3078 teeth) aged 18 to 65 years. When evaluating the CBCT results, the presence of calcifications and obliteration of the pulp chamber were taken into account. The prevalence of these lesions was analyzed depending on gender, age, tooth type, dental status and periodontal diseases. The median and interquartile range were used to describe the quantitative data. Comparison of quantitative variables was performed using the nonparametric Kruskal-Wallis and Mann-Whitney tests. Categorical variables are presented as absolute values and percentages and their comparison was performed using Fisher’s exact test or the Chi-squared test. The nonparametric Spearman rank correlation test was used to assess the correlation. The statistical significance of differences was accepted at p < 0.05. RESULTS. Calcifications were detected in 63 (61.76%) patients in 276 (8.96%) teeth. Obliteration of the pulp chamber was detected in 86 (84.31%) patients in 445 (14.46%) teeth. A statistically significant positive correlation was found between age and obliteration of the pulp chamber (r = 0.44; p-value < 0.001), as well as the amount of calcifications (r = 0.24; p-value = 0.015). Analysis of cases of obliteration and calcifications depending on gender, the presence or absence of periodontal diseases, and dental status did not reveal statistically significant differences. CONCLUSIONS. Calcifications and obliteration of pulp chamber were found in more than half of the patients. Their number increases with age, and in women occurs more often than in men. They were most often detected in the first molars. For a dentist, data on the prevalence of calcifications and mineralization of pulp chamber are one of the key aspects for planning high-quality root canal treatment.